2020
DOI: 10.1590/0001-3765202020191562
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and toxicological evaluation of two anti-asthmatic polyherbal formulations

Abstract: The study aim was to evaluate the toxic potential of two polyherbal formulation i.e. " PH 1 & PH 2" and scientific validation of their anti-asthmatic use. Acute oral toxicity study as per OECD 425 TG was conducted. For validation of anti-asthmatic claim, in vivo assay named Ovalbumin (OVA)-induced murine method in Wistar rats was used. Eosinophils and IgE antibody were quantified post-administration of low and high doses of the formulations. No mortality was observed in acute toxicity study. Elevated levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Herbal remedies come in a variety of formats, such as tinctures, pills, and topical preparations. They are frequently tailored to the specific needs and symptoms of the patient Saleem et al (2020). These formulations have long been utilized to treat liver illnesses throughout cultures, and new research has demonstrated encouraging outcomes in their hepatoprotective properties with few adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal remedies come in a variety of formats, such as tinctures, pills, and topical preparations. They are frequently tailored to the specific needs and symptoms of the patient Saleem et al (2020). These formulations have long been utilized to treat liver illnesses throughout cultures, and new research has demonstrated encouraging outcomes in their hepatoprotective properties with few adverse effects.…”
Section: Introductionmentioning
confidence: 99%